Changes in Caesarean Delivery Rates in Western Australia from 1995 to 2010 by Gestational Age at Birth. Issue 4 (July 2015) - Einarsdóttir, Kristjana; Ball, Stephen; Pereira, Gavin; Griffin, Christopher; Jacoby, Peter; de Klerk, Nick; Leonard, Helen; Stanley, Fiona J.
Abstract Background The caesarean delivery rate in the developed world has been increasing. It is not well understood how caesarean delivery rates have changed by gestational age at birth in Western Australia, particularly in relation to the introduction of the early‐term delivery guidelines in Australia in 2006. Methods Data from the Western Australian Midwives Notification System were used to identify 193 136 singletons born to primiparous women at 34–42 weeks' gestation during 1995–2010. Caesarean delivery rates were calculated by gestational age group (34–36 weeks, 37–38 weeks, and 39–42 weeks) and stratified into pre‐labour and in‐labour caesarean delivery. The average annual per cent change (AAPC) for the caesarean delivery rates was calculated using joinpoint regression. Log‐binomial regression was used to estimate the risk of having a caesarean delivery while adjusting for maternal and antenatal factors. Results Caesarean delivery rates rose steadily from 1995 to 2005 (AAPC = 5.9%, [95% confidence interval (CI) 4.9, 6.9]), but stabilised since then (AAPC = 0.9%, [95% CI −1.9, 3.8]). The rate of in‐labour caesarean deliveries rose consistently from 1995 to 2010 across all gestational age groups. The pre‐labour caesarean delivery rate rise was most dominant at 37–38 weeks' gestation from 1995 to 2005 (AAPC = 6.8%, [95% CI 5.4, 8.2]), but declined during 2006–10 (AAPC = −4.5, [95% CI −6.7, −2.3]), while at the same time the rate at 39–42 weeks rose slightly. Conclusions The rise in pre‐labour caesarean deliveries during 1995–2005 occurred predominantly at 37–38 weeks' gestation, but declined again from 2006 to 2010. This suggests that the recently developed Australian early‐term delivery guidelines may have had some success in reducing early‐term deliveries in Western Australia.